Detection and characterization of protein oligomeric species by light scattering methods: myosin light chain kinase supramolecular structures - Filenko, A.M. (Биополимеры и клетка, 2000)
Modern multi-angle light scattering, fast protein liquid chromatography and laser correlation spectroscopy used together give rather complete information about the distribution of different protein particles in solution and their characteristics. The data received by these methods on smooth muscle myosin light chain kinase (MLCK) as the object of investigation suggest that MLCK exists in solution as a mixture of oligomeric, dimeric and monomeric particles which contents at ionic strength close to physiological constitute 2, 53 and 45 wt. % correspondingly. An important point is that supramolecular kinase species content in eluate from a gel filtration column was much higher than their content at equilibrium. The contributions of oligomer, dimer and monomer in eluate at the exit from the column were 5.3, 81.5 and 13.2 wt. % accordingly. All three kinase species are characterized by prolonged lifetime. The transition from pure dimer into equilibrium state lasts for about 10 min. The kinase dimer is a rod-like structure with molecular mass of about 2-10 kDa and root mean square (RMS) radius Rt 22 nm. Oligomer is characterized by RMS radius Rs 80 nm. Its structure may be presented as a helical ring containing JO kinase molecules per turn with a number of turns about 10. Another more realistic explanation of the data obtained involves a rod-like or elongated spiral model according to which 6 kinase molecules, arranged in line or elongated spiral, form one structural unit, which must be a real oligomer (hexamer). About 17 such structural units, associated in parallel, form aggregates with molecular mass of about 101 kDa. Kinase spiral hexamer fits well the structure of smooth myosin filament with which the kinase is in close contact in vivo. Preliminary experiments with a number of other proteins (myosin, myosin subfragment 1, bovine serum albumin, chemotrypsin, papain) showed that all of them form supramolecular structures with prolonged time of transition from pure species to equilibrium distribution of monomers and supramolecular structures. Сучасні методи багатокутового світлорозсіювання в поєднанні зі швидкісною хроматографією білків та лазерною кореляційною спектроскопією дають досить детальну інформацію щодо розподілу білкових частинок у розчині, їхнього розміру та молекулярної маси. Дані, отримані при дослідженні кінази легких ланцюгів міозину гладеньких м'язів, свідчать про те, що цей білок існує в розчині як рівноважна суміш олігомерних, дймерних та мономерних часток у кількісному співвідношенні 2, 53 та 45 вагових % відповідно. На виході з гель-фільтраційної колонки рівновага значно зсунута в бік олігомерних форм кінази і час переходу до рівноважного стану становить приблизно 10 хв. Димер кінази має стрижнсвидну структуру з середньоквадратичним радіусом (СКР) біля 22 нм. Для олігомеру СКР складає біля 80 нм. Його структуру можна представити у вигляді спірального кільця із 10 витків з 10 молекулами кінази на виток. Структуру олігомера добре описують також стрижневидна або спіралевидна моделі з шістьма молекулами, розміщеними вздовж лінії або витягну тої спіралі. Біля 17 таких шестимолекулярних елементів утворюють паралельно асоційовані агрегати. Попередні до слідження показали, що низка інших білків також існує в розчині як рівноважна суміш мономерів і надмолекулярних структур з тривалим часом життя. Современные методы многоуглового свсеторассеяния совместно со скоростной хроматографией белков и лазерной корреляционной спектрскопией дают достаточно полную информацию о распределении белковых частиц в растворе, их размере и молекулярной массе. Данные, полученные при исследовании киназы легких цепей миозина гладких мышц, свидетельствуют, что этот белок существует в растворе как равновесная смесь олигомерных, димерных и мономерных частиц в количественном соотношении 2, 53 и 45 весовых % соответственно. На выходе из гель-фильтрационной колонки равновесие сильно сдвинуто в сторону олигомерных форм киназы и время перехода в равновесное состояние составляет приблизительно 10 мин. Димер киназы имеет стержневидную структуру со среднеквадратичным радиусом (СКР) около 22 нм. Для олигомера СКР составляет около 80 нм. Его структуру можно представить в виде спирального кольца из 10 витков с 10 молекулами киназы на виток. Структуру олигомера хорошо описывают также стержневидная или спиралевидная модели с шестью молекулами, размещенными вдоль линии или вытянутой спирали. Около 17 таких шестимолекулярных элементов образуют параллельно ассоциированные агрегаты. Предварительные исследования показали, что ряд других белков также существует в растворе как равновесная смесь мономеров и надмолекулярных структур с продолжительным временем жизни.